Two-Dimensional Echocardiographic Right Ventricular Size and Systolic Function Measurements Stratified by Sex, Age, and Ethnicity: Results of the World Alliance of Societies of Echocardiography Study - Addetia, Karima; Miyoshi, Tatsuya; Citro, Rodolfo; Daimon, Masao; Gutierrez Fajardo, Pedro; Kasliwal, Ravi R.; Kirkpatrick, James N.; Monaghan, Mark J.; Muraru, Denisa; Ogunyankin, Kofo O.; Park, Seung Woo; Ronderos, Ricardo E.; et al. (Journal of the American Society of Echocardiography, 2021)
Echocardiographic assessment of right ventricular (RV) systolic function is an important component of clinical decision making. Although professional societies have worked to define normal ranges of RV size and function, their guidelines have not included the impacts of age, sex, and ethnicity on these parameters, as they have for the left ventricle. The World Alliance of Societies of Echocardiography study was designed to investigate the effects of age, sex, and ethnicity on all cardiac chambers. The aim of this study was to explore whether these differences exist for RV systolic parameters. Adequate two-dimensional RV-focused views for the measurement of systolic parameters, including fractional area change and global and free wall longitudinal strain, were available in 1,913 subjects (mean age, 47 ± 17 years; 51% men). Basal and mid-RV dimensions, length, tricuspid annular peak systolic excursion, tissue Doppler S′ velocity, and myocardial performance index were also measured. Subjects were grouped by age (<40, 41–65, and >65 years), with results also stratified by sex and ethnicity (Asian, black, or white) and analyzed using vendor-independent software. Differences among groups were evaluated using analysis of variance. Women had smaller absolute and indexed RV areas and absolute RV dimensions and higher magnitudes of fractional area change, free wall strain, and global longitudinal strain compared to men. With respect to age, most of the statistically significant differences were noted between the <40- and >65-year age groups, with RV areas and lengths smaller in older age groups and RV functional parameters (S′, fractional area change, tricuspid annular plane systolic excursion, global longitudinal strain, free wall strain, and myocardial performance index) showing minimal decreases or no changes with age. Although there were no meaningful differences in functional parameters among ethnic groups, RV size was smallest in Asians. These findings suggest that although two-dimensional RV parameters are age and sex dependent, association with race is less apparent, excepting that the Asian population appears to have smaller chamber sizes compared with whites and blacks. •Normal values of RV size and function were determined from 1,913 subjects.•Normal values of RV size and function differ by age and gender.•The Asian population has smaller chamber sizes compared with whites and blacks.